Spontaneous dipolar Bose-Einstein condensation on the surface of a cylinder - Young-S, Luis E.; Adhikari, S. K. [UNESP] (American Physical Society (APS), 2023)
We demonstrate the spontaneous formation of a Bose-Einstein condensate (BEC) of strongly bound harmonically trapped dipolar Dy164 atoms on the outer curved surface of an elliptical or a circular cylinder, with a distinct topology, employing the numerical solution of an improved mean-field model including a Lee-Huang-Yang-type interaction, meant to stop a collapse at high atom density, the axis of the cylindrical-shell-shaped BEC being aligned along the polarization direction of the dipolar atoms. These states are dynamically stable and a Gaussian initial state leads to the cylindrical-shell-shaped state in both imaginary-time and real-time propagation. The formation of the hollow cylindrical BEC by a real-time simulation starting from a solid cylindrical state demonstrate the possibility of the formation of such a condensate experimentally.